Simplified Method to Compute the Influence of PV Generation and Electric Vehicles in an Energy Community - Comitre Bueno, Alejandro; Martín-Rivas, Sebastián (IEEE, 2026)
An energy community with photovoltaic generation and electric vehicles is considered in this study. The main contribution is the use of overlapping functions (PV generation with demand, PV generation with electric vehicles, and electric vehicles with demand) that allow us to obtain explicit analytical formulas that relate system parameters to the outcomes of interest. For example, how the results of optimal photovoltaic capacity to be installed or net profit relate to the EV connection pattern, energy prices, or facility amortization costs. The theoretical development of the method is provided and applied to several case studies, for which graphs of some of the relevant outcomes are shown.
Artículo de 6 páginas (doble columna), presentado en ponencia oral en inglés en el congreso internacional con revisión por pares "2025 6th International Conference on Clean and Green Energy Engineering (CGEE)" celebrado en Zagreb (Croacia) del 23 al 25 de agosto de 2025.
La política editorial de IEEE para las contribuciones a congresos publicadas exige un embargo de 24 meses. https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/#accepted.
Keywords: Energía fotovoltaica - Generación; Vehículos eléctricos; Energy community; Fotovoltaic generation; Electric vehicle; Overlapping function; Net profit